DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH DALAM MATERI PERHITUNGAN KIMIA PADA SISWA KELAS XI SMA - Sophia, Ayya; Enawaty, Eny; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the problem solving ability in chemical calculation material in XI class students of SMAN 10 Pontianak. This research method was descriptive study with instrument in the form of 6 problem solving in essay. The subject were students of SMAN 10 Pontianak in XI IPA 1 students academic year 2016/2017 consisted of 38 students. The results showed that the average percentage of problem solving ability in chemical calculation material in XI IPA 1 students of SMAN 10 Pontianak were : (1) determining the number of molecules of a substance if known volume at temperature and certain pressure the amount of 76,76%, (2) calculating the number of moles of a substance at standard temperature and pressure (STP) the amount of 84,67%, (3) calculating the gas volume at constant pressure the amount of 41,67%, (4) determining a molecular formula of a compound the amount of 48,67%, (5) calculating the element level in a compound the amount of 80%, (6) predicting the volume of gas produced in a reaction at room temperature and pressure (RTP) the amount of 36,33%.Â Â Â Keywords: Problem Solving Ability, Chemical Calculation